South African Higher Education Institutions at the Beginning of the Covid-19 Pandemic: Sense-Making and Lessons Learnt - du Plessis, Marieta; Jansen van Vuuren, Carel D.; Simons, Abigail; Frantz, José; Roman, Nicolette; Andipatin, Michelle (Frontiers in Education, 2022)
After the unprecedented changes experienced in higher education due to the Covid-19 pandemic, there is a need to integrate initial thoughts and reflective experience to decide on the way forward. This study aimed to reflect on, and make sense of the events related to South African higher education institutions HEIs at the onset of the COVID-19 pandemic by using the Cynefin framework. Data from a rapid review of online media at the onset of the Covid-19 pandemic and a collaborative autoethnography session one year since lockdowns were implemented are used to present perspectives for the sense-making process. This offers insights to both ends of the spectrum as it highlights the evolution of processes taking place at multiple levels from government policies to institutional practices, as well as how this impacted on both staff and students. The Cynefin framework demonstrated sense-making efforts in the disordered, to the chaotic, to the complex, then to the complicated and eventually to the simple domain. Each domain ushered in its peculiarities and highlighted the issues ranging from vulnerabilities experienced in the higher education sector, to trying to reconfigure the academic year, to dealing with wicked problems, to eventually relying on expert assistance to navigate the virtual university space. Trying to establish causality in the simple domain proved challenging as the information available during the time was sparse. Despite these challenges, the lessons learnt include the importance of the sense-making process among all academic staff, the significance of collaboration and team efforts and the need to adapt leadership and self-leadership approaches to the changed ways of working in higher education institutions.